Shamba showdown: Ukama Ustawi- Progress Report #6a - Odera, Daniel; Kigo, Samm; Girvetz, Evan; Chilambe, Pedro; Waswa, Boaz (2024)
The majority of development funding today in Africa’s agriculture sector is understandably focused on small shareholder farmers. There are programs designed to increase yields through precision farming technologies, and there are programs designed to increase resilience through crop selections, or to increase income through access to markets and data. However, none of these programs address the looming food crisis coming in the next decade from a very different problem: The Youth Today, 85% of Kenya’s food supply is domestically grown or produced. We have one of the lowest food import ratios in the world. Most of that food is grown on local farms operated on a small scale by family farmers with less than 3ha of land. Less than 25% of Kenya’s food supply is grown on industrial scale commercial farms. However, any reasonably successful farmer in Kenya sends their children to urban boarding schools for a better education. Those children have no desire to go back to the farms. According to a recent study by Heifer International, less than 21% of agriculture focused organizations interviewed in Africa indicated encouraging youth as a core initiative. This creates a major issue since the median age of farmers in Kenya is now over 60 years old. In ten years, many of these farmers will no longer be able to run their farms. Focused on their personal / family situation rather than the macro economy, many of the next generation will allow the land to go fallow or use it to build their family an “upcountry house”. This situation is not unique to Kenya and can be seen in rural farming communities around Africa. In order to ensure food security for the coming decade and beyond, we need to find a way to “Make Farming cool again” such that today’s youth see it as a viable, attractive career option. At the very least, we need to give the urban youth an understanding of how to run their family farms remotely by phone, using local hired labor. The Shamba Showdown project leverages the fun interactive nature of 3D competitive games in order to address both of these goals.